Efeitos audiológicos e estudo do comportamento em trabalhadores de gráficas expostos a ruído e tolueno - Bitu, Carlene de Souza (2017)
The ototoxicity caused by medication has been a concern for the audiologists for many years and, more recently, the one caused by chemical agents, especially in the work environment. The challenge for the audiology is to detect and early diagnose of the hearing loss. The term Occupational Hearing Loss has been used since the beginning of the 90’s taking into account not only the Noise-induced hearing loss, but also all the other kinds of hearing loss that can be caused by the exposure to different risk factors in the workplace, such as chemical agents – aromatic solvent (toluene, xylene, benzene), metals (lead, arsenic and mercury) and some asphyxiating (carbon monoxide and butyl nitrite). OBEJECTIVE: investigate the audiological effects in the printing workers’ behavior when exposed to noise and toluene, as well as identify the workers’ behavior related to hearing loss prevention. METHODOLOGY: it was a quantitative cross-section study done in four printing industries in Teresina – PI, approved by the Ethic and Research Committee (Nº 1.376.499). There were two groups: Group I – 29 printing workers exposed to noise and toluene; and Group II with 30 administrative workers non-exposed to this kind of occupational risks. They answered the questionnaire (translated to Portuguese) “Beliefs and Attitudes on Hearing Loss Prevention by National Institute for Occupational Safety and Health” that talks about the beliefs, attitudes and behaviors of the hearing loss prevention and they also underwent a test battery comprising: pure-tone audiometry, immittance audiometry, otoacoustic emission and the hippuric acid biochemical examination, the main toluene metabolite on individuals exposed to toluene. RESULTS: male represented 62,71% with 29% in the printing function, followed by the receptionists (16,9%) and administrative assistants (10,2%). Hearing loss is present on the right ear in 12% of the individuals and 10% on the left ear. 16,9% of the sample has bilateral or unilateral hearing loss. The Noise-Induced Hearing Loss represents 10,2% of all the losses. In the tympanometry, almost all the ears had type A tympanogram, indicating the functioning of the middle ear function as normal. 94,92% of type A tympanogram was for right ear and 98,31% for left ear; the stapedial muscle reflex was present in 56 (94,92%) individuals in both ears and only one (5,08%) individual had not presented the reflex. The hippuric acid evaluation of the exposed group showed the lower level of 0,10 g/g creatinine and the higher level of 0,88% g/g, being within acceptable reference values. In relation to the otoacoustic emission, 48% of the answers are negative considering both ears, which means that at least one of the frequencies shows modification of the negative response. The exposed group shows 65% for negative responses and the control group shows 67% for positive responses. The average score for each question on the A and B version of the questionnaire that evaluates the belief of the workers, their attitudes facing the occupational noise and the hearing loss prevention practices showed a reduction in the mean scores, evidencing improvement on the workers’ information level with p= < 0,05. CONCLUSION: the individuals when exposed to noise presented an isolated sensorineural hearing loss in a frequency range that varies from 3000Hz to 8000Hz on both ears and on bilateral profound sensorineural loss. The hippuric acid examination showed results of hippuric acid rates within the normal standards established by the present rules of the country. Furthermore, the behavior of these workers facing the occupational noise and the preventive practices of hearing loss showed an increase on their knowledge level after they went through a training about the importance of prevention and the use of hearing protection equipment, reducing the risk of a noise-induced hearing loss.